Lasers Applications in Science and Industry - Jakubczak, Krzysztof (IntechOpen, 2011)
The book starts with basic overview of physical phenomena on laser-matter interaction. Then it is followed by presentation of a number of laser applications in the nano-particles and thin films production, materials examination for industry, biological applications (in-vitro fertilization,tissue ablation) and long-range detection issues by LIDARs.